2021
DOI: 10.1186/s12889-021-11562-6
|View full text |Cite
|
Sign up to set email alerts
|

Unmet needs for social support and diabetes-related distress among people living with type 2 diabetes in Thai Binh, Vietnam: a cross-sectional study

Abstract: Background Diabetes-related distress (DRD) refers to negative emotional and affective experiences from daily demands of living with diabetes. People who received social support seem less likely to experience DRD. The prevalence of T2D in Vietnam is rapidly increasing. Yet, DRD and its association with social support have not been investigated. This study investigates DRD and how it is associated with unmet needs for social support in people with T2D in Thai Binh Province, Vietnam. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 29 publications
3
8
0
Order By: Relevance
“…Vietnam. The previous study further reported that the risk of developing DRD increased with number of types of unmet needs for social support [8]. The increased risk of DRD among individuals with multiple unmet needs aligns with the results in the present study.…”
Section: Characteristicssupporting
confidence: 92%
See 4 more Smart Citations
“…Vietnam. The previous study further reported that the risk of developing DRD increased with number of types of unmet needs for social support [8]. The increased risk of DRD among individuals with multiple unmet needs aligns with the results in the present study.…”
Section: Characteristicssupporting
confidence: 92%
“…Characteristics of the total sample and distributions of individuals with DRD are presented in Table 1. As we have been reporting in a previous study [8] we found that among the 806 individuals with an age of 40 or above, 50.0% (n=403) presented with DRD. Approximately half of the included individuals were female (52.7%) and found that being female had a statistically significant association with DRD (OR: 2.17, CI95%: 1.64-2.88).…”
Section: General and Socio-economic Characteristics Of Individuals Wi...supporting
confidence: 82%
See 3 more Smart Citations